Scientific Substantiation of the Development-Evolution of New Man Founded on High-Quality Interaction Energy Created by Using Harmony, Ethical Canons and Holistic Principles - Iryna Suvorova, Nickolay Suvorov (European Journal of Sustainable Development, 2017)
The study’s focus is on cognising the methods of formation of New Man, a new reasoning, a new worldview, and an ERA of PEACE and LOVE by in-depth research into the content of ethical- moral rules, regulations, principles, and canons based on the Great Cosmic Laws of Development, and the Harmony Laws of the CREATOR and GOD. This is the strategy of holistic sustained development of Man and Humanity in the Epoch of Aquarius. The authors’ research is built around the following axioms: - Energy is the unique essence of All Being; - EVERYTHING is reduced to energy – the energy of inner and external interaction. Keywords: holistic principles, energy of inner and external interaction, harmony, spirituality, ethics